A compact construction for non-monotonic key-policy attribute-based encryption. (2019) - Zhang, Junqi; Gao, Haiying
The attribute-based encryption (ABE) scheme with monotonic access structure cannot deal with an access structure that is associated with the negation of attributes, which is not convenient for real world applications. In this paper, we attempt to propose a more expressive non-monotonic ABE scheme through a new method. To achieve this goal, we firstly propose a linear two-mode identity-based broadcast encryption (TIBBE) scheme based on an identity-based broadcast encryption (IBBE) scheme. We introduce the concept of identity-based revocation (IBR) for this scheme without increasing the size of parameters in IBBE. The scheme is selective identity secure under the m-DBDHE assumption. Then, we convert the TIBBE scheme into a non-monotonic key-policy attribute-based encryption (KP-ABE) scheme with compact parameters. Our KP-ABE scheme could achieve constant-size ciphertexts, and the scale of the private keys grows linearly with the scale of the attribute set. Besides, the computational cost is the lowest compared with other existing non-monotonic KP-ABE schemes.